Penerapan teknologi hijau dalam arsitektur kampus: Studi kasus pembangunan gedung fakultas pada lingkungan tropis di malang - astuti, dyas fajar (Maliki Interdisciplinary Journal, 2025)
In tropical climate zones, sustainable architecture demands a harmonious integration of passive design strategies and green technologies to achieve optimal energy efficiency and thermal comfort. This study explores the implementation of environmentally conscious solutions including cross ventilation, reflective roofing, photovoltaic systems, and thermal insulation materials within the context of a campus building at UIN Malang. The focal point of the case study is a newly proposed faculty building, assessed through energy performance and thermal comfort simulations tailored to Malang’s climatic conditions. Findings reveal that combining passive architectural approaches with active technological systems can reduce cooling energy consumption by up to 25% compared to conventional building models. Based on these results, the study recommends several design strategies: precise building orientation, adaptive shading mechanisms, integration of solar energy systems, and the use of locally sourced materials with high insulation properties. These measures collectively contribute to advancing the vision of a sustainable and environmentally friendly campus.